Internalization of Islamic Education Values in the Mabbarsanji Tradition in the Bugis Community, Masakambing Village, District. Masalembu District. Sumenep - Evin, Evin; Dewi Nurhayati (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
The Mabarsanji tradition in Masakambing Village is an Islamic cultural heritage that functions as a means of internalizing the values of Islamic education, especially in the aspects of faith, morals, social and morals. Initially only carried out in commemoration of the Prophet's birthday, this tradition developed and became part of various religious events. Its uniqueness lies in the influence of Madurese culture and the involvement of the entire community in its implementation. However, there are still challenges in understanding the contents of the book Al-Barzanji. This research aims to examine the values of Islamic education in Mabarsanji so that this tradition is not only preserved, but also its meaning is understood. This study examines the internalization of Islamic educational values within the Mabborsanji tradition in the Bugis community of Masakambing Village. The focus includes the implementation, the Islamic values contained within, and the process of internalization within local wisdom. This tradition plays a role in the learning of faith, morality, and social values for the local community. This study employed a qualitative method with a descriptive approach. Data were collected through interviews with religious and community leaders, as well as direct observation of the Mabborsanji tradition and documentation. Data analysis employed the Miles & Huberman model, which encompasses data reduction, data presentation, and conclusion drawing. Data validity was checked using source and technique triangulation. The results of this study indicate that Islamic educational values, such as love for the Prophet Muhammad (peace be upon him), exemplary morals, and worship and social values, are indirectly taught through the Mabborsanji tradition. Internalization of these values is achieved through a habitual approach, daily life experiences, and the role of religious and family leaders in providing a deeper understanding. This tradition also plays a role in strengthening social ties and strengthening their Islamic identity